Amido-Functionalized Magnetic Metal−Organic Frameworks Adsorbent for the Removal of Bisphenol A and Tetracycline - Zhang, Guangpu; Wo, Rong; Sun, Zhe; Xiao, Lei; Liu, Guigao; Hao, Gazi; Guo, Hu; Jiang, Wei (Frontiers in Chemistry, 2021)
In this paper, amido-functionalized MOFs with core/shell magnetic particles (Fe3O4@MIL-53(Al)-NH2) was prepared by the solvothermal method and characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared (FT-IR), Vibrating Sample Magnetometer (VSM) and UV/VIS spectrophotometer. The influence of different factors on the adsorption effect of the pollutant, including adsorbent amounts, adsorption time, ionic strength and pH, were explored. It was found that the amine-decorated Fe3O4@MIL-53(Al)-NH2 were efficient for removal of contaminant, with the adsorption capacity for bisphenol A (234.1 mg/g) and tetracycline (84.8 mg/g) under the optimized conditions. The adsorption kinetics and the equilibrium adsorption data indicated that the adsorption process of BPA and TC was more compatible with the pseudo-second-order kinetic model and the Langmuir model, respectively. The thermodynamic values show the adsorption of the mentioned contaminant was spontaneous and endothermic. Moreover, the Fe3O4@MIL-53(Al)-NH2 adsorbent had good regeneration and reusability capacity after five cyclic utilization. All these results show Fe3O4@MIL-53(Al)-NH2 adsorbent could be a potential candidate for future water purification.